UNCONVENTIONAL FRACTIONATION RADIOTHERAPY REGIMENS IN TREATMENT OF INOPERABLE LUNG CANCER - D. V. Gogolin; I. A. Gulidov; K. E. Medvedeva; Y. A. Ragulin; Y. S. Mardinsky; I. N. Ivanova; L. V. Kursova; I. I. Kotuhov; A. Y. Buksha (Сибирский онкологический журнал, 2019)
The purpose of the study was to compare the efficacy and toxicity of hypofractionated versus hyperfractionated radiotherapy in patients with inoperable lung cancer.Material and Methods. Patients with inoperable lung cancer, who were treated between 2014 and 2017, were assigned to undergo radiotherapy in two arms: accelerated hypofractionated conformal radiotherapy arm with 70 patients (60 Gy in 25 fractions, with 2.4 Gy per fraction) and accelerated hyperfractionated radiotherapy with 49 patients (60–70 Gy with 1–1.5 Gy per fraction). At the same time, platinum-based chemotherapy was applied.Results. The rates of partial response, complete response, stable disease and progressive disease were 44.3, 7.2, 38.5 and 10.0 %, respectively in patients with hypofractionated conformal radiotherapy arm. The corresponding values were 71.4, 6.1, 16.4 and 6.1 %, respectively in patients with hyperfractionated radiotherapy arm. The 2-year overall survival rate was 62.8 % for the hypofractionated group and 58.1 % for the hyperfractionated group. Esophagitis III grade was observed in 4 (5.7 %) patients of the hypofractionated group and in 3 (6.5 %) patients of the hypofractionated group. Pneumonitis III grade was reported in 2 (2.9 %) patients in the hypofractionated radiotherapy arm and in 4 (8.7 %) patients in the hyperfractionated radiotherapy arm.Conclusion. Results of the study showed that 3D-conformal hypofractionated radiotherapy combined with concurrent chemotherapy resulted no in severe radiation-induced complications, and demonstrated satisfactory short-and long-term treatment outcomes.